PENGEMBANGAN BUKU PINTAR CEPAT BACA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA ANAK KELAS 1 SEKOLAH DASAR - Yulia Kurnia Arif; Nurhaningtyas Agustin (PREMIERE : Journal of Islamic Elementary Education, 2021)
This research is aims to develop teaching materials that meet the needs of students. This teaching material as a learning support to improve students' reading skills so that students are able to read and write. This textbook is in the form of “Quick Read Smart Books”. The procedure for developing this fast-reading smart book consists of three stages, namely Define, Design, Develop. This smart book was assessed by two validators, namely a media expert validator and a material expert validator to determine the feasibility of the product. Then carried out the observation of the implementation of learning to obtain data and determine the practicality of the product. Furthermore, there are pretest-posttest questions and student response questionnaires to determine the effectiveness of the product.